Effect of Phytase on the Growth Performances of Growth of Laying Hens (Warren) - Bohoua, Guichard L.; Yelakan, Clarisse K. Kone (International Journal of Poultry Science, 2007)
This study consists of supplementing the feeding of laying hens with phytase at various proportions and evaluating its influence on the average weight and the index of consumption. The experiment was led during 6 weeks on 4 batches of 50 laying hens. These batches respectively received a supplementation of 0 G/kg food (pilot batch), 1.36 g/kg (batch 1), 2.72 g/kg (batch 2), 4.05 g/kg (batch 3). Each week the laying hens are weighed and the feeding efficiency index calculated. The results revealed that the best batch was batch one in terms of profit of weight gained the feeding efficiency index.